First report of Leptonectes (Ichthyosauria: Leptonectidae) from the Lower Jurassic (Pliensbachian) of Asturias, northern Spain - Fernández, Marta Susana (2018)
Early Jurassic ichthyosaurs are well-known based on the abundant and exquisitely preserved European records of the Western Tethys. For example, faunas from Southern England and the Toarcian Posidonia shales of Holzmaden and surrounding areas (Germany) are known worldwide. However, between these areas there are still gaps and/or under-sampled localities from the northern coast of Europe. In recent years as a result of systematic palaeontological and geological explorations of Pliensbachian fossiliferous localities along the coast of Asturias (northern Spain), ichthyosaur specimens have been collected. One of them can be identified at lower taxonomic levels and it is referred to Leptonectes sp. These new findings highlight the richness of the fossil record of the northern coast of Spain and suggest that the abundance of Pliensbachian ichthyosaurs worldwide may have been underestimated.